Milestones to reach Hepatitis C Virus (HCV) elimination in Italy: From free-of-charge screening to regional roadmaps for an HCV-free nation. Issue 2 (February 2022) - Kondili, Loreta A.; Aghemo, Alessio; Andreoni, Massimo; Galli, Massimo; Rossi, Alessandro; Babudieri, Sergio; Nava, Felice; Leonardi, Claudio; Mennini, Francesco Saverio; Gardini, Ivan; Russo, Francesco Paolo
Abstract: Although Italy has been on track for Hepatitis C Virus (HCV) elimination since 2019, it fell off track due to the decrease in the number of treated patients. HCV elimination in Italy will be possible if immediate action is taken. A health policy was implemented beginning in 2021, consisting of screening among key populations and birth cohorts (1969–1989), estimated to have a high prevalence of undiagnosed individuals. The active screening requires regional governance that manages the processes' complexity integrating a well-organized network between territory assistance and hospital to achieve an effective HCV care cascade. This document aims to support the regional decision-making process by defining paths for screening and linkage-to-care. Implementing active screening strategies beyond a risk-based approach is required as a General Practitioners' task. Simplified paths must be drawn for the key populations screening. The infrastructure built for COVID-19 vaccination could be used also for HCV screening. According to a multidisciplinary care delivery, screening should be supplemented with rapid linkage-to-care and treatment of newly diagnosed patients. The realization of the proactive screening during the first two years is vital because it will define the tracks for the whole HCV cost-effective screening of 1948–1988 birth cohorts in Italy.